2013
DOI: 10.1109/tip.2012.2236343
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality Assessment Using Multi-Method Fusion

Abstract: A new methodology for objective image quality assessment (IQA) with multi-method fusion (MMF) is presented in this paper. The research is motivated by the observation that there is no single method that can give the best performance in all situations. To achieve MMF, we adopt a regression approach. The new MMF score is set to be the nonlinear combination of scores from multiple methods with suitable weights obtained by a training process. In order to improve the regression results further, we divide distorted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(106 citation statements)
references
References 23 publications
0
105
0
1
Order By: Relevance
“…In the table, the best three results for a given benchmark are written in boldface, results not reported are denoted by "-". Some measures are not benchmark independent, i.e., their authors reported evaluation results on the benchmark that took part in the development of the measure without providing results for other benchmarks, or prepared a one IQA measure for each benchmark, also without cross-benchmark tests, e.g., [24], [26], [27], [29], [30], [31], [35], [36]. Results for approaches that are not dataset independent were excluded from comparison, they are written in italics in the table.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the table, the best three results for a given benchmark are written in boldface, results not reported are denoted by "-". Some measures are not benchmark independent, i.e., their authors reported evaluation results on the benchmark that took part in the development of the measure without providing results for other benchmarks, or prepared a one IQA measure for each benchmark, also without cross-benchmark tests, e.g., [24], [26], [27], [29], [30], [31], [35], [36]. Results for approaches that are not dataset independent were excluded from comparison, they are written in italics in the table.…”
Section: Discussionmentioning
confidence: 99%
“…A conditional Bayesian mixture of experts model with a support vector machines classifier was used in [30] for combining SSIM, VSNR, and VIF using k-nearest-neighbour regression. A support vector regression approach was shown in [31]. In [32], in turn, image blocks were first classified using decision trees and then FSIM [13], mean squared error, and different variations of PSNR [33] were combined.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the distortion types include noise, blur, compression, transmission, and intensity deviation, which are involved in the open IQA datasets [24]. Their parameters are standard deviation of noise N , standard deviation of blur kernel B , bit rate of per pixel BPP , transmission signal-to-noise ratio SNR , and intensity change value V I , respectively.…”
Section: Distortionmentioning
confidence: 99%
“…MAD [48] and MMF [57,59] are representatives for multiple strategies and MMF, respectively. Especially for the latter one, appropriate fusion of existing metrics opens the chances to build on the strength of each participating metric and the resultant framework can be even used when new, good metrics emerge.…”
Section: B) Multiple Strategies or Mmf Approachesmentioning
confidence: 99%